Measurement report: Influence of particle density on secondary ice production by graupel and frozen drop collisions - S. Yadav; L. Metten; P. Grzegorczyk; A. Theis; S. K. Mitra; M. Szakáll (Atmospheric Chemistry and Physics)
Collision-induced fragmentation of atmospheric ice particles is a crucially important but understudied secondary ice production mechanism in clouds. We present a laboratory study dedicated to fragmentation due to graupel–graupel and frozen drop–frozen drop collisions and the role of these collisions in augmenting the ice particle concentration in clouds. For this, graupel particles of different sizes and densities were created utilizing dry growth conditions in a cold chamber at −7 and −15 °C using a setup that simulates the natural rotation and tumbling motion of freely falling graupel. Ice spheres, as proxies for frozen drops and ice pellets, were generated by freezing purified water in 3D-printed spherical molds. We conducted collision experiments inside the cold chamber utilizing a fall tube that ensures the central and repeatable collision of ice particles at different collision kinetic energies. The number of fragments generated in the collisions was analyzed, following a theoretical framework, as a function of the collision kinetic energy. The detection limit of our experiments was 30 µm; thus, fragments with sizes lower than 30 µm could not be detected. The observed number of fragments varied between 1 and 20 and was, thus, comparable to or higher than the number of fragments resulting from drop freezing experiments. Our results revealed a strong dependency of the fragment number on the density of the colliding ice particles, which can be attributed to the particles' structure. The sizes of the fragments that we detected were in the submillimeter range for graupel and up to 3 mm for ice spheres. Another set of experiments, focusing on the multiple collision of graupel revealed that the number of fragments generated decreases significantly and approaches zero when a particle undergoes more than three collisions in a row.